Hannah Arendt’s Politics of Women in the Perspective of Philosophy - Hastanti Widy Nugroho (Jurnal Perempuan, 2017)
The article entitled “Hannah Arendt’s Politics of Women in the Perspective of Philosophy” derived from the results of philosophical research. The research objective is specifically exploring the philosophical concept of Hannah Arendt’s politics of women and revealthe forms of implementation in the context of open access, participation, and political control those are involving the women. Hannah Arendt political concept subsequently is applied to be adopted as a political strategy to fight for political equality of women in Indonesia. Concept, form of implementation, and women’s political strategy is analyzed through library research by using the typical elements of philosophical research; interpretation, deduction and induction, historical continuity, idealization, heuristics, and inclusive language. By using the typical elements of philosophical research, it is found that the source of women political thought isoriginating from Hannah Arendt’s idea of labor. The idea lies in a private area which is regarded as the political basis of reproductive and the strength of birthrate. In addition, Hannah Arendt introduced the politics of women as a feminine ethics which is conceptuallydefined as the ability to forgive and to love. The politics of women at the praxis level, according to Hannah Arendt should emphasize the principle of equality in the public sphere and apply the typical feminine power.